MIRERC 064/2025: ASSESSMENT OF MENTAL HEALTH INEQUALITIES, ACCESS TO MENTAL HEALTH SERVICES IN SAMBURU EAST SUB -COUNTY , KENYA - Satonik, Lekilit Jacob; Dr. Dorothy Kagendo Kithinji; Dr. Patrick Kinyua Kubai, (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
From a global perspective, mental health is believed to be caused by scientific issues and environmental factors. But locally, many individuals have a firm belief that mental health disorders are caused by cultural beliefs and possession by evil spirits. More so in Samburu East Sub-County, beliefs that mental health disorders are caused by supernatural beings are on the rise. This study aims to investigate the current state of mental health inequalities and access to mental healthcare services in Samburu East Sub-County, Kenya. Other objectives include determining the types of selected mental health disorders prevalent in Samburu East and identifying socio-economic factors influencing mental health inequalities in Samburu East. Data collection methods to be used in this study will be a cross-sectional descriptive study with sequential mixed methods to determine the inequalities in prevalence of mental health disorders and access to health care services in the Sub-County, Kenya. We will collect both qualitative and quantitative data through interviews, surveys, and focus group discussions with community members, health workers, and traditional healers. The expected outcomes of this study are that people of Samburu East are not getting the required care because of a lack of knowledge and a belief that mental illness is caused by supernatural factors. Also, it is expected that findings will expose gaps in mental health infrastructure, workforce shortages, and limited awareness of existing services. Cultural stigma and marginalization, compounded by poverty and lack of implementation of national mental health policies, will be the key barriers to mental health equity in the region. These findings will be important in informing local policy and care models that respect cultural context while promoting access to scientifically grounded mental health care.